Psychological Distress in Elite Sambo and Recreational Athletes - Tubić, Tatjana; Živanović, Bogdan; Lakićević, Nemanja; Zenić, Nataša; Gilić, Barbara; Rudas, Eduardas; Eliseev, Sergey; Trivić, Tatjana B.; Bianco, Antonino; Drid, Patrik (Frontiers in Psychology, 2022)
Both elite and recreational athletes experience stress on a daily basis. Yet, the professional sport might help individuals to cope better with stressful events, particularly elite-level sport. One hundred five were elite sambo athletes, and 140 recreational athletes were recruited for the purpose of the present study. The Depression Anxiety Stress Scales-21 were used to assess psychological distress in different domains such as depression, anxiety, and stress. Based on the identified prevalence within obtained results, psychological distress in sambo athletes is observed, and they are vulnerable to a range of mental health issues that may be related to both sport and non-sport factors. Moreover, results showed gender and specific-sport dependence of examined mental health problems. Females were found to be a vulnerable subsample, especially recreational female athletes, not elite-level ones. Future epidemiological and interventional studies should explore optimal strategies to identify mental health needs based on specific sport activity, especially in gender.